2013
DOI: 10.1021/ac401424j
|View full text |Cite
|
Sign up to set email alerts
|

Fluorous Membrane Ion-Selective Electrodes for Perfluorinated Surfactants: Trace-Level Detection and in Situ Monitoring of Adsorption

Abstract: Ion-selective electrodes (ISEs) with fluorous anion-exchanger membranes for the potentiometric detection of perfluorooctanoate (PFO(-)) and perfluorooctanesulfonate (PFOS(-)) were developed. Use of an anion-exchanger membrane doped with the tetraalkylphosphonium derivative (Rf8(CH2)2)(Rf6(CH2)2)3P(+) and an optimized measurement protocol resulted in detection limits of 2.3 × 10(-9) M (1.0 ppb) for PFO(-) and 8.6 × 10(-10) M (0.43 ppb) for PFOS(-). With their higher selectivity for PFO(-) over OH(-), membranes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
73
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 73 publications
(73 citation statements)
references
References 52 publications
0
73
0
Order By: Relevance
“…We found that fluorous systems exhibit substantially improved ion selectivities as compared to non‐fluorous ISE membranes, which has also resulted in remarkably low detection limits . Electrodes with fluorous membranes have been successfully applied for the detection of several analytes, not only in simple aqueous samples but also in biologically relevant systems such as bacterial growth media, lake and river water containing natural organic matter, and Ottawa Sand suspensions . Here we discuss the lifetime of pH sensors with ionophore‐doped fluorous sensing membranes when exposed to hot caustic solutions as they are used in CIP treatments.…”
Section: Introductionmentioning
confidence: 99%
“…We found that fluorous systems exhibit substantially improved ion selectivities as compared to non‐fluorous ISE membranes, which has also resulted in remarkably low detection limits . Electrodes with fluorous membranes have been successfully applied for the detection of several analytes, not only in simple aqueous samples but also in biologically relevant systems such as bacterial growth media, lake and river water containing natural organic matter, and Ottawa Sand suspensions . Here we discuss the lifetime of pH sensors with ionophore‐doped fluorous sensing membranes when exposed to hot caustic solutions as they are used in CIP treatments.…”
Section: Introductionmentioning
confidence: 99%
“…The achieved detection limit is significantly lower than the reported values: around tens of parts per billion to parts per million levels from the HPLC-FLD [54] and GC-ECD [8,64] techniques, 10 ppb from the colorimetric assay (10 ppb) [14], and 0.07 ppb obtained using fluorous membrane ion-selective electrodes [13]. As known, the concentration of total PFCs in natural water samples is in the range of tenths to hundreds of parts per trillion [7,13,15,65,66]. Currently, only application of LC-MS/MS allows better detection limit to be obtained for PFOA/PFO À analysis (0.01 ppte0.01 ppb), combined with preconcentration [67].…”
Section: Analytical Performance Of Ecl Detection Of Pfoamentioning
confidence: 62%
“…However, these methods often require complicated pretreatment steps and expensive labor resources. Recently, fluorous membrane ion-selective electrodes [13] and colorimetric sensor using mixed poly(ethylene glycol) and perfluorinated thiols modified gold nanoparticles [14] for the detection of PFCs have been reported, respectively, but limited by the laborious preparation procedures, cost and efficiency. Therefore, a simple, cheap and sensitive analytical method for fast prescreening of PFOA residues is urgently needed.…”
Section: Introductionmentioning
confidence: 99%
“…0.01 ppb) based on the response of three times the standard deviation of zero-dose response (n¼ 6). The detection limit obtained is significantly lower than that of the HPLC-FLD (Poboży et al, 2011) and GC-ECD (Scott et al, 2006;Dufkova et al, 2009) techniques (around tens of parts per billion to parts per million levels), superior to that of the colorimetric assay (10 ppb) (Niu et al, 2014), and also lower than that obtained using fluorous membrane ionselective electrodes ( $ 0.07 ppb) (Chen et al, 2013) (comparison of different methods for PFOA sensing listed in Table S1). Our findings indicate that the proposed PEC sensor is remarkably reliable for the determination of PFOA.…”
Section: Analytical Performance Of Visible-light-activated Pec Detectmentioning
confidence: 90%
“…It can be frequently found worldwide in surface waters and animal tissues (Lindstrom et al, 2011). Owing to its global ubiquity, ability to bioaccumulate in wildlife, extreme stability offered by the extremely strong carbon-fluorine bonds and difficulty to degrade, PFOA has aroused a tremendous environmental and health concern (Xu et al, 2013;Giesy and Kannan, 2001;Chen et al, 2013;Ohno et al, 2014). Therefore, rapid determination of PFOA residues has become highly desirable.…”
Section: Introductionmentioning
confidence: 99%